Pengaruh Penambahan Kompos Kotoran Sapi dan FABA Terhadap Karakteristik Kimia pada Tanah Berpasir dan Pertumbuhan Tanaman Tomat: The Effect of Cow Manure Compost and Fly Ash-Bottom Ash (FABA) Addition on the Chemical Properties of Sandy Soil and Tomato Growth - Nurul Faoziah; Iskandar; Gunawan Djajakirana (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2022)
Sandy soil has a low: ability of water retention, aggregate stability, and nutrient content. To improve its quality a mixture of compost and fly ash-bottom ash (FABA) need to be added to this soil. This study was aimed to determine the effect of compost and FABA as an ameliorant on the chemical properties of sandy soil and plant growth of tomato (Solanum lycopersicum). The pot experiment was carried out at Cikabayan Greenhouse, IPB University using a Completely Randomized Design with seven treatments and two replications. Each 5 kg of sandy soil per pot were mixed with cow manure compost and FABA at various doses. The test plant was tomato variety SL 975. Parameters of soil chemical properties were observed for organic-C, total N, available P, CEC, and exchangeable bases. Plant growth was observed at five weeks after planting (WAP). The A6 treatment, i.e. addition of 1,950 gram compost pot-1 and 25 gram FABA pot-1, showed the highest organic-C content in the soil (3.83%) as well as the plant height, leaf number, and fresh weight by 54.4 cm, 21 sheet, and 68.7 gram.